Teachers’ Perceptions of Correlated Science Lesson Planning in Single-Teacher and D1 Schools under the Peninsular Regional Education Directorate (2023–2024) - López Gamboa, Marco Vinicio (2025)
In single-teacher schools and those classified as EGB-1 (D1), their multigrade nature—where multiple grade levels are grouped within a single classroom—creates the need for subject-specific correlated lesson planning adapted to this context. This study aims to describe teachers’ perceptions of correlated Science lesson planning in institutions under the Peninsular Regional Education Directorate (DREPE), highlighting their implementation experiences during 2023 and 2024. This qualitative, descriptive study was conducted using a multiple case study approach. Semi-structured interviews were conducted with teachers from single-teacher and D1 schools, and the collected perceptions were manually coded and organized into categories and subcategories based on the teacher professional knowledge base (TPKB) of Gess Newsome’s PCK model (2015). Key findings include the limited preparation received in universities, the lack of time for lesson planning, the alignment of lesson plans with current classroom needs, and teachers’ requests for greater support from Costa Rica’s Ministry of Public Education. Consequently, the study recommends further integration of this type of planning into university teacher training programs, as well as increased provision of instructional resources to facilitate its development.